2009
DOI: 10.1002/gcc.20646
|View full text |Cite
|
Sign up to set email alerts
|

Loss of 16q in high grade breast cancer is associated with estrogen receptor status: Evidence for progression in tumors with a luminal phenotype?

Abstract: Loss of the long arm of chromosome 16 (16q) is observed in the vast majority of low grade/grade I (GI) invasive ductal carcinomas of no special type (IDC-NSTs), whereas this event is uncommonly seen in high grade/grade III (GIII) IDC-NSTs. Together with data on the pathology and genetics of breast cancer recurrences, this has led to the proposal that GI and GIII breast cancers evolve through distinct genetic pathways and that progression from GI to GIII is an unlikely biological phenomenon. We compared the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 56 publications
6
71
1
1
Order By: Relevance
“…This observation suggests that cases harbouring PPM1D gene amplification may display a 'firestorm' pattern (ie, tumours whose genome is characterized by multiple, clustered high-level amplifications). 9,41,42 Re-analysis of the data from Natrajan et al 9 revealed that all cases harbouring PPM1D gene amplification (n ¼ 8) displayed a 'firestorm' profile (Supplementary Figure 1). 9 Taken together, it is plausible that amplification of 17q23.2 may stem from a global pattern of genetic instability that favours the acquisition of multiple, high-level gene amplifications throughout the genome.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that cases harbouring PPM1D gene amplification may display a 'firestorm' pattern (ie, tumours whose genome is characterized by multiple, clustered high-level amplifications). 9,41,42 Re-analysis of the data from Natrajan et al 9 revealed that all cases harbouring PPM1D gene amplification (n ¼ 8) displayed a 'firestorm' profile (Supplementary Figure 1). 9 Taken together, it is plausible that amplification of 17q23.2 may stem from a global pattern of genetic instability that favours the acquisition of multiple, high-level gene amplifications throughout the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these prognostic signatures highlighted the fact that ER-positive cancers are a spectrum of lesions ranging from those with very low proliferation (as defined by microarrays) and good outcome to those with high microarray-defined proliferation and poor outcome. On the other hand, ER-negative cancers seem to constitute a collection of distinct entities, underpinned by distinct molecular aberrations [88,139,140], whose prognosis is possibly governed by biological phenomena other than proliferation. Recent studies have revealed that ER-negative cancers with high expression of immune response genes may have an outcome better than other ERnegative cancers [111,141,142], suggesting that distinct prognostic signatures for specific subgroups of breast cancer may be necessary to accurately define their outcome.…”
Section: B Weigelt Et Almentioning
confidence: 99%
“…DNA was extracted as previously described [12]. DNA concentration was measured with Picogreen Ò according to the manufacturer's instructions (Invitrogen, Paisley, UK).…”
Section: Nucleic Acid Extractionmentioning
confidence: 99%
“…We microdissected and analysed a series of 48 GIII invasive ductal carcinomas of no special type (IDC-NSTs) with high resolution microarray-based comparative genomic hybridisation (aCGH) and mRNA expression arrays. Our study focused on GIII IDC-NSTs only to avoid bias introduced by distinct patterns of genetic aberrations between grade I and III cancers [12] and between invasive ductal carcinomas and special types [14][15][16].…”
Section: Introductionmentioning
confidence: 99%